2017
DOI: 10.1080/20477724.2017.1375708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characterisation of respiratory syncytial viruses circulating in Bulgaria during the 2014/15 and 2015/16 winter seasons

Abstract: The respiratory syncytial virus (RSV) is a leading cause of acute respiratory illnesses (ARI) in infants and young children. The objectives of this study were to investigate the RSV circulation among children aged <5 years in Bulgaria, to identify the RSV-A and RSV-B genotypes and to perform an amino acid sequence analysis of second hypervariable region (HVR2) of the G gene. During the 2014/15 and 2015/16 winter seasons, nasopharyngeal specimens of 610 children aged <5 years with ARI were tested using Real Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 62 publications
4
24
0
Order By: Relevance
“…Nonetheless, a true comparison of RSV prevalence in different geographic areas is difficult to perform taking into account the differences in the study design and, even in our study, prevalence was wide-ranging according to the season. Bronchiolitis and pneumonia were significantly associated with RSV-positive cases among children aged < 5 years, which was consistent with previous studies that found RSV as a major cause of acute LRTI in this age group [12,[38][39][40][41].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nonetheless, a true comparison of RSV prevalence in different geographic areas is difficult to perform taking into account the differences in the study design and, even in our study, prevalence was wide-ranging according to the season. Bronchiolitis and pneumonia were significantly associated with RSV-positive cases among children aged < 5 years, which was consistent with previous studies that found RSV as a major cause of acute LRTI in this age group [12,[38][39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…The alignment of the predicted amino acid sequences of strains from BA9, NA1 and ON1 genotypes confirmed the relatively high genetic variability associated with the HVR2. Strains from both of subtypes showed common changes, conserved N-glycosilation sites and subtitutions leading to loss or gain of these sites that had been previously reported [11,40,41,45,46,49,50,[54][55][56][57][58][59]. Within RSV-A strains, the number of substitutions among ON1 strains was higher compared with its NA1 counterparts.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Neutralizing antibodies are secreted against both proteins [ 40 ]. However, based on the genetic variability of the G protein, the RSV A is subdivided into 15 strains (GA1–7, SAA1, NA1–4 CB-A, and ON1–2) [ 41 ], while the RSV B group is subdivided into 24 strains (SAB1–4, BA1–12, GB1–4, GB5/CB1, CBB, and URU1–2) [ 42 , 43 ]. Thus, the infectivity, immunological resistance, and viral genetic drift (spontaneous mutation) may be important in the patterns of seasonal circulation and genetic evolution of RSV genotypes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on genetic variations in G protein, HRSV is divided into two groups: group A which is categorized into 14 genotypes (GA1 to GA7, SAA1, CB-A, NA1 to NA4 and ON1) and group B which is subdivided into a further 27 genotypes (BA1 to BA12, BA-C, SAB1 to SAB4, GB1 to GB4, URU1 to URU2, CB-B, CB-1, BA-CCB and BA-CCA) [2,4]. The subtype ON1 of RSV-A was first identified in Canada in December of 2010 and was reported to contain a unique duplication of 72 nucleotides in the second hypervariable region of the G gene [5] and it may be spreading rapidly and replacing the NA1 subtype in many countries such as Saudi Arabia, South Korea, Italy, Germany, Bulgaria, Croatia and China [6][7][8][9][10][11][12][13]. A similar duplication was reported in the variable region around 60 nucleotide of the G protein of the BA subtype of RSV-B in 1999 in Argentina [14].…”
Section: Introductionmentioning
confidence: 99%